2018
DOI: 10.1093/mnras/sty158
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diffusion in hot subdwarf progenitors from the common envelope channel

Abstract: Diffusion of elements in the atmosphere and envelope of a star can drastically alter its surface composition, leading to extreme chemical peculiarities. We consider the case of hot subdwarfs, where surface helium abundances range from practically zero to almost 100 percent. Since hot subdwarfs can form via a number of different evolution channels, a key question concerns how the formation mechanism is connected to the present surface chemistry. A sequence of extreme horizontal branch star models was generated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Models of stellar evolution were computed using the computer program mesa (Paxton et al 2011(Paxton et al , 2013(Paxton et al , 2015(Paxton et al , 2018. The methods adopted and parameter space explored closely follow the previous paper by Byrne et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Models of stellar evolution were computed using the computer program mesa (Paxton et al 2011(Paxton et al , 2013(Paxton et al , 2015(Paxton et al , 2018. The methods adopted and parameter space explored closely follow the previous paper by Byrne et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has investigated the effects of atomic diffusion and radiative levitation in particular on the evolution of a post-common envelope star as it evolves from the red giant branch (RGB) to the extreme horizontal branch (EHB) following the onset of helium burning in the core (Byrne et al 2018). Here we expand the analysis of these simulations to include searches for pulsations in pre-EHB models.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that atmospheric subdwarf metal abundances have little or virtually no memory of their parent main sequence abundances (e.g. Moehler 2001;Németh et al 2012;Byrne et al 2018). Metals at the subdwarf surface vary by large amounts depending on previous binary evolution and diffusion processes, leading to diverse abundance patterns (e.g.…”
Section: Atmosphere Structurementioning
confidence: 99%
“…The models by Michaud et al (2011) can not reproduce the Heenrichment and CNO-cycle pattern observed in some sdBs (and the sdOs discussed here) since they use approximated methods to evolve their models through the He-flash. Byrne et al (2018) have preformed similar calculations for post common envelope sdBs from the top of the RGB to the zero age HB with a more self-consistent treatment of the He-flash. They produced He-rich atmospheres in their delayed He-flash models and predict C and N to be enriched and O to be depleted for sdBs on the zero-age horizontal branch (ZAHB).…”
Section: Diffusionmentioning
confidence: 99%